Kandungan Lemak Telur Itik Asin dengan Pemeraman Menggunakan Kulit Jeruk Manis (Citrus sinensis: Salted Duck Egg Fat Content with Repaining Using Sweet Orange Peel - Andi Anggun Dwi Utami Darwis; Irmawaty Majid; Handayani Indah Susanti; Muhammad Basir Paly; Sohrah (Universitas Islam Negeri Alauddin Makassar, 2023)
The community’s need for food of animal origin increases in line with economic development, change in healthy lifestyles and awareness of health so that people tend to consume highly nutritious and healthy foods such as eggs. But eggs contain high levels of fat. To overcome this, duck eggs are preserved by ripening using sweet orange peel. This study aims to determine the fat content of salted duck eggs during ripening using sweet orange peel. This research method used a completely randomized design (CRD), namely 5 treatments (0%, 15%, 30%, 45% and 60% sweet orange peel extract) each with 2 replications. Tools and materials used are basins, analytical scales, jars, sandpaper, stove, pots, knives, plastic, labels, 40 duck eggs, 1. 250 ml of water, 1,200 grams of rubbing ash, 2,000 grams of bricks, 2,000 grams of salt and 720 grsweet orange peel. Parameters tested for salted duck egg fat content by ripening using sweet orange peel. Data analysis used Analysis of Variance (ANOVA). The results of the study found that the addition of sweet orange peel extract had no significant effect (P>0.05) on the fat content of salted duck eggs.